Micropulse cyclophotocoagulation in the treatment of primary open-angle glaucoma and congenital glaucoma. Part 1: hypotensive effect mechanisms, modern procedure protocol - O. V. Ermakova; E. A. Ragozina (Российский офтальмологический журнал)
Micropulse cyclophotocoagulation (MP-CPC) refers to interventions that reduce intraocular pressure by laser exposure on the ciliary body, while the term “coagulation” in its name does not reflect the essence of the procedure, but is inherited from the previous continuous laser version. Unlike other methods that target ciliary body, MP-CPC is considered the safest procedure due to its special laser action mode and the absence of a coagulative effect. In the first part of our review, we would like to focus on the history, mechanisms of action and procedure protocol of micropulse cyclophotocoagulation.